PERBEDAAN BERPIKIR KRITIS DAN PEMAHAMAN KONSEP DENGAN SNOWBALL THROWING DAN SNOWBALL DRILLING - Husein, Ramadhika Farhan (Yayasan Amanah Nur Aman, 2021)
Penelitian ini bermaksud guna mengetahui perbedaan kemampuan berpikir kritis dan kemampuan pemahaman konsep matematika siswa yang diajar dengan menggunakan model pembelajaran Kooperatif Tipe Snowball Throwing dan model pembelajaran Kooperatif Tipe Snowball Drilling di kelas XI SMA Negeri 1 Kutacane. Penelitian ini secara kuantitatif, dengan jenis penelitian quasi eksperimen. Populasi penelitiannya adalah semua kelas XI SMA Negeri 1 Kutacane tahun ajaran 2021-2022 dengan jumlah 8 kelas. Sampel yang digunakan oleh peneliti adalah kelas XI IPA Inti 1 dan XI IPA Inti 2 dengan cara cluster random sampling yang masing-masing kelas berjumlah 30 siswa untuk dijadikan kelas eksperimen I dan II. Instrumen tes menggunakan tes berbentuk uraian. Analisis data dilakukan dengan cara analisis varians. Hasil temuan ini menunjukkan: Terdapat perbedaan kemampuan berpikir kritis matematika siswa yang diajar dengan model pembelajaran Kooperatif Tipe Snowball Throwing dengan model pembelajaran Kooperatif Tipe Snowball Drilling pada materi Program Linear; Terdapat perbedaan kemampuan pemahaman konsep matematika siswa yang diajar dengan model pembelajaran Kooperatif Tipe Snowball Throwing dengan model pembelajaran Kooperatif Tipe Snowball Drilling pada materi Program Linear; Terdapat perbedaan kemampuan berpikir kritis dan kemampuan pemahaman konsep matematika siswa yang diajar dengan model pembelajaran model pembelajaran Kooperatif Tipe Snowball Throwing dan model pembelajaran Kooperatif Tipe Snowball Drilling pada materi Program Linear. Kata Kunci : Berpikir Kritis; Pemahaman Konsep; Snowball Throwing; Drilling. ABSTRAK This study aims to determine the difference between critical thinking skills and the ability to understand mathematical concepts of students who are taught using the Snowball Throwing Type Cooperative learning model and the Snowball Drilling Cooperative learning model in class XI SMA Negeri 1 Kutacane. This research is quantitative, with a quasi-experimental type of research. The research population is all class XI SMA Negeri 1 Kutacane for the academic year 2021-2022 with a total of 8 classes. The sample used by the researcher was class XI IPA Core 1 and XI IPA Core 2 by means of cluster random sampling with 30 students in each class to be used as experimental classes I and II. The test instrument uses a test in the form of a description. Data analysis was carried out by means of analysis of variance. These findings indicate: There are differences in students' critical thinking skills in mathematics taught by the Cooperative learning model of Snowball Throwing Type and the cooperative learning model of the Type of Snowball Drilling in the Linear Program material; There are differences in the ability to understand mathematical concepts of students who are taught with the Cooperative learning model of the Snowball Throwing Type and the cooperative learning model of the Snowball Drilling Type on the Linear Program material; There are differences in critical thinking skills and the ability to understand mathematical concepts of students who are taught with the Snowball Throwing Type Cooperative learning model and the Snowball Drilling Cooperative learning model in the Linear Program material. Keywords: Critical Thinking; Concept Understanding; Snowball Throwing; Drilling.